Continuity in general practice and hospitalization patterns: an observational study - Wensing, Michel; Szecsenyi, Joachim; Laux, Gunter (BMC family practice, 2021)
High continuity of care is a key feature of strong general practice. This study aimed to assess the effect of a programme for enhancing strong general practice care on the continuity of care in Germany. The second aim was to assess the effect of continuity of care on hospitalization patterns.
Gesehen am 19.02.2021